2005
DOI: 10.1088/0022-3727/38/11/002
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in microcavity plasma devices and arrays: a versatile photonic platform

Abstract: Selected highlights in the recent development of microplasma devices are reviewed with emphasis on large arrays of Si-based hybrid plasma/semiconductor pixels. Arrays of 40 000 (200 × 200) pixels, excited by sinusoidal ac waveforms at frequencies of 5-20 kHz, have now been realized. The fabrication of these arrays and their electrical and optical performance with rare gases and Ar/N 2 mixtures are briefly described. Metal/dielectric/metal devices having a piezoelectric dielectric (BaTiO 3 ), a cylindrical micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 11 publications
2
42
0
Order By: Relevance
“…the integral optical efficiency [3,5,2]. Experimental investigations of the composing single discharge cavities are challenging, primarily due to the small dimensions and the operating conditions close to atmospheric pressure.…”
Section: Confidential: Not For Distribution Submitted To Iop Publishmentioning
confidence: 99%
“…the integral optical efficiency [3,5,2]. Experimental investigations of the composing single discharge cavities are challenging, primarily due to the small dimensions and the operating conditions close to atmospheric pressure.…”
Section: Confidential: Not For Distribution Submitted To Iop Publishmentioning
confidence: 99%
“…Radio frequency (rf) excited MDs are also being studied for use in lighting and surface modification [10][11][12]. For example, Eden et al [13] demonstrated MD sources operating at 5-20 kHz using rare gas and Ar/N 2 mixtures in large-arrays of up to 40 000 pixels.…”
Section: Introductionmentioning
confidence: 99%
“…They can be also used for monitoring of various inflammatory skin diseases. Since 'calor' (temperature) forms one of the components of inflammation; detecting changes in the temperature of the skin can be used for monitoring of diseases like atopic dermatitis, psoriasis, mycosis fungoides, etc [118].…”
Section: Diagnostic Applicationsmentioning
confidence: 99%
“…They can be also used for monitoring of various inflammatory skin diseases. Since 'calor' (temperature) forms one of the components of inflammation; detecting changes in the temperature of the skin can be used for monitoring of diseases like atopic dermatitis, psoriasis, mycosis fungoides, etc [118].Gold nanoparticles have been studied for nanodiagnosis. A large number of techniques are available which can help in tracing of gold nanoparticles like fluorescence, optical absorption, electrical conductivity, atomic and magnetic force.…”
mentioning
confidence: 99%